Cross-continental differences in Black-tailed Godwit breeding densities are best explained by arthropod abundance in the chick-hatching period - Silva-Monteiro, M.; Pehlak, H.; Timonen, S.; Pessa, J.; Pasanen, E.; Verhoeven, M.A.; Loonstra, A.H.J.; Piersma, T.; Robin, F.; Korniluk, M.; Onwezen, M.; Bongers, M.; et al. (Journal of Ornithology, 2022)
The endangered continental Black-tailed Godwit ( Limosa limosa limosa ) is a migratory ground-nesting wader breeding in a wide variety of open, wet habitats across Europe. Conservation research has concentrated on the causes of population decline, but we know surprisingly little about whether any resources limit local breeding populations and if so, whether these are resources for the adults or the chicks. We collected data from 63 key breeding sites in five countries across Europe to test whether, after correcting for differences in surveyed areas, the size of Godwit breeding populations was related to environmental variables (vegetation biomass, soil moisture) or food resources for adult birds (soil invertebrates) or chicks (vegetation dwelling arthropods) measured during different times of the reproductive cycle. We found the number of Godwit territories to be positively related to arthropod abundance during the chick-hatching period. We found additional, weaker support for a positive relation between Godwit territory numbers and the abundance of soil-dwelling invertebrates (mostly earthworms) at clutch laying, but not at chick-hatching. These relationships were observed across countries, while we found little support for relationships within countries, possibly due to the smaller range in conditions that exist within countries. Both vegetation growth and soil moisture weren’t related to Godwit territory numbers. Our results suggest that food abundance for chicks, and to a lesser extent adult birds, are key factors determining the size of local Godwit breeding populations. Conservation management aiming to enhance local Godwit populations should therefore consider the impacts of management strategies on the arthropod prey of chicks.